1996
DOI: 10.1289/ehp.96104s15
|View full text |Cite
|
Sign up to set email alerts
|

Fish models for environmental carcinogenesis: the rainbow trout.

Abstract: Progress over the past 30 years has revealed many strengths of the rainbow trout as an alternative model for environmental carcinogenesis research. These include low rearing costs, an early life-stage ultrasensitive bioassay, sensitivity to many classes of carcinogen, a well-described tumor pathology, responsiveness to tumor promoters and inhibitors, and a mechanistically informative nonmammalian comparative status. Low-cost husbandry, for example, has permitted statistically challenging tumor study designs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(122 citation statements)
references
References 138 publications
3
115
1
3
Order By: Relevance
“…Investigations of the causes of epizootics of skin and liver neoplasia occurring in fish from polluted environments have most often implicated polycyclic aromatic hydrocarbons (PAHs) as etiologic agents (19). Among numerous fish species studied, the most complete and detailed mechanistic and dose-response studies regarding a wide array of carcinogens have been performed in rainbow trout (4). Various small aquarium fish species have been utilized as carcinogenesis models including the guppy, sheepshead minnow, Rivulus, and medaka (7,24,33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the causes of epizootics of skin and liver neoplasia occurring in fish from polluted environments have most often implicated polycyclic aromatic hydrocarbons (PAHs) as etiologic agents (19). Among numerous fish species studied, the most complete and detailed mechanistic and dose-response studies regarding a wide array of carcinogens have been performed in rainbow trout (4). Various small aquarium fish species have been utilized as carcinogenesis models including the guppy, sheepshead minnow, Rivulus, and medaka (7,24,33).…”
Section: Introductionmentioning
confidence: 99%
“…Following aqueous exposure to DMBA as fry, stomach, liver, gas bladder, and kidney are target tissues, with decreasing incidences of epithelial neoplasia in these tissues in the order listed (15,20). Dietary exposure of rainbow trout to DMBA results in primarily gastric neoplasia and lesser incidences of liver and gas bladder neoplasia (4). A single mesenchymal neoplasm, a fibrosarcoma of the liver, occurred in rainbow trout administered BAP by intraperitoneal injection at 10 months of age (27) (20).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of fish to mycotoxins is variable, and the rainbow trout species exhibits more sensitivity (Bailey et al, 1996). Arana et al (2002) showed that the trout genotype can significantly affect the effect of aflatoxins on growth parameters and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Some well-documented neoplasms include viral-induced dermal sarcomas in walleyes and aflatoxin-associated hepatocellular adenomas and carcinomas in rainbow trout as well as a variety of sporadic tumors in numerous species. 1,2,12 This report details spontaneous ocular and cutaneous tumors in multiple fresh and marine teleost species with features characteristic of neuronal embryonal tumors.Neuronal embryonal tumors arise from neuroectodermal progenitor cells within subependymal matrix layers and have morphology and aggressive behavior in common.10 Tumor types include medulloepitheliomas, neuroblastomas, retinoblastomas, ependymoblastomas, and primitive neuroectodermal tumors (PNETs). PNETs are derived from pluripotent germinal neuroepithelial cells and may be further classified on the basis of anatomic location as medulloblastomas, cerebral PNETs, or peripheral neuroectodermal tumors.…”
mentioning
confidence: 98%
“…Some well-documented neoplasms include viral-induced dermal sarcomas in walleyes and aflatoxin-associated hepatocellular adenomas and carcinomas in rainbow trout as well as a variety of sporadic tumors in numerous species. 1,2,12 This report details spontaneous ocular and cutaneous tumors in multiple fresh and marine teleost species with features characteristic of neuronal embryonal tumors.…”
mentioning
confidence: 98%